The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1088/1361-6595/ab4e61
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CO2 microwave plasma based on the phenomenon of skin-depth-limited contraction

Abstract: The sub-atmospheric CO 2 microwave plasma is known to contract to a narrow filament with rising pressure as result of a mode transition. This changing state of contraction is investigated in relation to its dielectric properties, in order to directly relate the discharge parameters to the discharge radius. The electron density and gas temperature are measured, respectively, by 168 GHz microwave interferometry and Doppler broadening of the 777 nm oxygen emission lines. The plasma is operated in steady state wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
126
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(141 citation statements)
references
References 40 publications
(114 reference statements)
10
126
0
Order By: Relevance
“…It was indeed demonstrated, both experimentally (e.g., van Rooij et al, 2015;Bongers et al, 2017;den Harder et al, 2017;van den Bekerom et al, 2019;Wolf et al, 2019Wolf et al, , 2020 and computationally (e.g., Berthelot and Bogaerts, 2017;Heijkers and Bogaerts, 2017;Kotov and Koelman, 2019), that in practice, the vibrational non-equilibrium is not the leading mechanism in (sub)atmospheric MW or GA CO 2 plasmas, and that the CO 2 conversion is thermal, although Pietanza et al (2020) suggested to act with caution on this assumption, as their model still showed clear deviations from equilibrium, even at temperatures of 3,500-5,500 K.…”
Section: Improving the Energy Efficiencymentioning
confidence: 73%
See 4 more Smart Citations
“…It was indeed demonstrated, both experimentally (e.g., van Rooij et al, 2015;Bongers et al, 2017;den Harder et al, 2017;van den Bekerom et al, 2019;Wolf et al, 2019Wolf et al, , 2020 and computationally (e.g., Berthelot and Bogaerts, 2017;Heijkers and Bogaerts, 2017;Kotov and Koelman, 2019), that in practice, the vibrational non-equilibrium is not the leading mechanism in (sub)atmospheric MW or GA CO 2 plasmas, and that the CO 2 conversion is thermal, although Pietanza et al (2020) suggested to act with caution on this assumption, as their model still showed clear deviations from equilibrium, even at temperatures of 3,500-5,500 K.…”
Section: Improving the Energy Efficiencymentioning
confidence: 73%
“…In MW and GA plasmas, the electron temperature is still higher than the gas temperature (hence, they are not really thermal plasmas), but the vibrational and gas temperature are often close to each other (i.e., VT equilibrium), so they can also be considered as quasi-thermal plasmas. For this reason, the CO 2 conversion proceeds mainly by thermal reactions in MW and GA plasmas at practical operating conditions (van Rooij et al, 2015;Berthelot and Bogaerts, 2017;Bongers et al, 2017;den Harder et al, 2017;Heijkers and Bogaerts, 2017;Kotov and Koelman, 2019;van den Bekerom et al, 2019;Wolf et al, 2019Wolf et al, , 2020.…”
Section: Different Dissociation Mechanisms In Different Plasma Typesmentioning
confidence: 99%
See 3 more Smart Citations